Chapter Pervasività della signoria - Carocci, Sandro (Reti Medievali E-Book, 2023)
The article examines two explicitly different meanings of the expression 'pervasiveness of lordship'. The first moves from the more commune meaning of pervasiveness, understood as a synonym of capillary diffusion, to distinguish between areas of seigniorial centrality and areas of seigniorial marginality in late medieval Italy. The second meaning understands "pervasiveness" in a less usual sense, i.e. as the capacity of lordship to thoroughly penetrate the surrounding world. After describing this notion of pervasiveness, the article illustrates some examples, drawn from various late medieval Italian regions, of lordships without pervasiveness and of pervasive lordships, questioning the capacity of seigniorial pervasiveness to survive and reconfigure itself in the late Middle Ages.